PROSES IMPLEMENTASI TEKNOLOGIBARU, KONFLIK PERAN DAN GAYA KEPEMIMPINAN BERPENGARUH TERHADAP KINERJA KARYAWAN - Hanuni, Nanang; Yuniawan, Ahyar (JURNAL BISNIS STRATEGI, 2016)
The purpose of this research is to test the influences of leadership styleand new technology implementation on role conflictto impactemployee performance. Using these variables, the usage of these variables are able to solve the arising problem within officer Charoen Pokphand Semarang. Statement of this problem is how increase employee performance?.The samples size of this research is 135officerCharoen Pokphand Semarang. Using the Structural Equation Modeling (SEM). The results show that leadership styleand new technology implementationon role conflictto impact employee performance.The effect of leadership styleon role conflictare significant; the effect of leadership styleon employee performanceare significant; the effect of new technology implementationon role conflictare significant;the effect ofnew technology implementationon employee performanceare significant; the effect ofjob satisfactionon employee performanceare significant.